ANALYSIS OF CAREER DEVELOPMENT TO IMPROVE EMPLOYEE PERFORMANCE AT TYPE C CUSTOMS AND EXCISE KPU SOEKARNO HATTA - Ikhsannudin, Ikhsannudin; Ahyar, M Khairul; Suwandi, Eko; Nizami, Rachma; Muljadi, Muljadi (Jurnal Comparative: Ekonomi dan Bisnis, 2023)
Employee career development at the Soekarno Hatta Customs and Excise KPU Type C based on educational background, education and training in position, and employee tenure. Factors that influence career development at the Soekarno Hatta Customs and Excise KPU Type C are Managerial Competence (managerial ability), Technical/functional Competence (technical ability), Creativity (creativity). Career paths can be passed by employees when the employee has high work performance as indicated by an increase in salary. A positive career attitude is carried out by the Soekarno Hatta Customs and Excise Commission Type C so that it is more in line with career demands and career opportunities that are consistent with the interests, values, needs and abilities of individuals. The career adaptability of the Type C KPU Customs and Excise Soekarno Hatta employees demonstrates the application of knowledge, expertise and the latest technology in their career paths. For the individual characteristics of Type C KPU Customs and Excise employees, Soekarno Hatta makes career choices on the basis of: Interests, Identity, Personality. Keywords: Career Development, Employee Performance, Education.